Past climate and continentality inferred from ice wedges at Batagay Highlands, interior Yakutia - Opel, Thomas; Murton, Julian B.; Wetterich, Sebastian; Meyer, Hanno; Ashastina, Kseniia; Günther, Frank (Dr.); Grotheer, Hendrik; Mollenhauer, Gesine; Danilov, Petr P.; Boeskorov, Vasily; Savvinov, Grigoriy N.; Schirrmeister, Lutz (Dr.) (Climate of the Past, 2019)
Ice wedges in the Yana Highlands of interior Yakutia - the most continental region of the Northern Hemisphere - were investigated to elucidate changes in winter climate and continentality that have taken place since the Middle Pleistocene. The Batagay megaslump exposes ice wedges and composite wedges that were sampled from three cryostratigraphic units: the lower ice complex of likely pre-Marine Isotope Stage (MIS) 6 age, the upper ice complex (Yedoma) and the upper sand unit (both MIS 3 to 2). A terrace of the nearby Adycha River provides a Late Holocene (MIS 1) ice wedge that serves as a modern reference for interpretation. The stable-isotope composition of ice wedges in the MIS 3 upper ice complex at Batagay is more depleted (mean delta O-18 about -35 parts per thousand) than those from 17 other ice-wedge study sites across coastal and central Yakutia. This observation points to lower winter temperatures and therefore higher continentality in the Yana Highlands during MIS 3. Likewise, more depleted isotope values are found in Holocene wedge ice (mean delta O-18 about -29 parts per thousand) compared to other sites in Yakutia. Ice-wedge isotopic signatures of the lower ice complex mean delta O-18 about -33 parts per thousand) and of the MIS 3-2 upper sand unit (mean delta O-18 from about -33 parts per thousand to -30 parts per thousand) are less distinctive regionally. The latter unit preserves traces of fast formation in rapidly accumulating sand sheets and of post-depositional isotopic fractionation.